SULTAN OF TERNATE ISKANDAR DJABIR SYAH: FROM MALINO CONFERENCE TO BECOME THE MINISTER OF HOME AFFAIRS OF EASTERN INDONESIA STATE (NEGARA INDONESIA TIMUR/NIT) 1946-1950 - Hasyim, Rustam (JURNAL ILMU BUDAYA, 2016)
This study aims to reconstruct the political participation of Iskandar Djabir Syah (the 47th Sultanof Ternate) in the establishment of the State of Eastern Indonesia. The study focuses on outliningsome political events involving Iskandar Djabir Syah such as the Malino and Denpasar conferencesand becaming the Minister of Home Affairs of the Eastern Indonesia State for 1949 to 1950 periods.The method used in this paper is a heuristic method that is history, criticism, interpretation andhistoriography. The results showed that: (1) the participation of Sultan of Ternate Iskandar DjabirSyah in the unitary state started in the early independence of the Republic of Indonesia; it wascharacterized by conducting Malino and Denpasar conferences in 1946. The establishment of theEastern Indonesia State became the political inspiration for Iskandar Djabir Syah to involve as thesenate member of the Eastern Indonesia State/NIT representing North Maluku, as well as one of itsdesigners. (2) As one of the leaders who agreed to the idea of van Mook to form a federalist countryin the Malino and Denpasar conference, so that when the Eastern Indonesia State was formed, he wasappointed as the Minister of Home Affairs in the cabinet of J.E. Tatengkeng for 1949 to 1950 periods.(3) Malino to Denpasar Conference in 1946 initiated by H.J. van Mook was the Dutch effort toestablish the states in order to realize the United States of Indonesia (Republik Indonesia Serikat/RIS)based on Linggarjati Agreement. At the conference, it was formed the Eastern Indonesia State(Negara Indonesia Timur/NIT) covering the areas of Sulawesi, Small Sunda (Bali and Nusa Tenggara)and the Maluku Islands.